2016
DOI: 10.3389/fphar.2016.00488
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Deoxypodophyllotoxin Disposition in Mouse, Rat, Monkey, and Dog by Physiologically Based Pharmacokinetic Model and the Extrapolation to Human

Abstract: Deoxypodophyllotoxin (DPT) is a potential anti-tumor candidate prior to its clinical phase. The aim of the study was to develop a physiologically based pharmacokinetic (PBPK) model consisting of 13 tissue compartments to predict DPT disposition in mouse, rat, monkey, and dog based on in vitro and in silico inputs. Since large interspecies difference was found in unbound fraction of DPT in plasma, we assumed that Kt:pl,u (unbound tissue-to-plasma concentration ratio) was identical across species. The prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 42 publications
(58 reference statements)
0
31
0
Order By: Relevance
“…The developed PBPK model successfully predicted plasma pharmacokinetics of DPT in mice, rats, monkeys, and dogs. Good predictions were also found for pharmacokinetics in tissues of mice (Chen et al, 2016). It is possible to gain a profound understanding of the dynamics of drug disposition in both plasma and tissues/organs through the PBPK model.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The developed PBPK model successfully predicted plasma pharmacokinetics of DPT in mice, rats, monkeys, and dogs. Good predictions were also found for pharmacokinetics in tissues of mice (Chen et al, 2016). It is possible to gain a profound understanding of the dynamics of drug disposition in both plasma and tissues/organs through the PBPK model.…”
Section: Introductionmentioning
confidence: 90%
“…Our previous studies have shown the metabolic kinetics of DPT in hepatic microsomes and its high plasma protein binding in various species (Chen et al, 2016;Xie et al, 2016). Demethylenated metabolite (M2) was shown to be the main metabolite of DPT (Chen et al, 2016;Xie et al, 2016). Subsequently, a whole-body physiologically based pharmacokinetic (PBPK) model of DPT including main organs of body was established on the basis of in vitro assays (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPT (purity > 99%) and DPT-HP-β-CD (content: 2.8%) were kindly provided by the Medicinal and Chemical Institute, China Pharmaceutical University (Chen et al, 2016). Paclitaxel (injection) was purchased from the Yangtze River Pharmaceutical Group (Jiangsu, China).…”
Section: Reagentsmentioning
confidence: 99%
“…As the promising microtubule inhibitor, DPT and its intravenous formulation of β-cyclodextrin inclusion complex (Zhu et al, 2010) have been adopted for phase I evaluation. A physiologically based pharmacokinetics model was also established for better efficacy and safety assessment (Chen et al, 2016). Previous studies have demonstrated that DPT exerts an anti-tumor effect on the human BC MDA-MB-231 cell line in vivo and in vitro (Benzina et al, 2015;Khaled et al, 2016).…”
Section: Introductionmentioning
confidence: 99%